City branding’s influence on social media engagement: The cool factor - Schivinski, B.; Li, X.; Alahmari, A. M.; Nguyen, Q. P.; Czarnecka, B.; Loureiro, S. M. C. (Journal of Product and Brand Management, 2026)
Purpose Consumers interact with city brands in diverse ways. Through city-related social media engagement, consumers actively shape a city’s brand meaning and communication strategies. Drawing on city branding aspects, defined as physical attributes, functional attributes and personality traits, this study aims to examine how perceptions of city brand coolness mediate the relationship between city branding aspects and social media engagement in terms of cognitive, emotional and behavioral engagement. Design/methodology/approach Data from an online survey conducted in Saudi Arabia of 537 consumers who actively follow their cities on social media platforms was analyzed using covariance-based structural equation modeling. Findings The findings reveal that city branding aspects directly influence social media engagement regarding emotion, cognition and behavior. Specifically, perceived city brand coolness mediates the relationship between city branding aspects, namely, physical attributes, functional attributes and personality traits, and cognitive and behavioral engagement on social media. Originality/value This study advances the branding literature by investigating the notion of brand coolness, which revolves around consumers using brands as instruments for self-expression. It explores the intricate mediational role of coolness in the relationship between city attributes and city-related social media engagement. The findings guide how city branding aspects influence residents’ engagement on social media in relation to their city. Implications for theory and practice related to co-creating city branding within the place branding industry are discussed, and suggestions for future studies are presented.